Zinc‐α2‐glycoprotein is associated with non‐albuminuric chronic kidney disease progression in type 2 diabetes: a retrospective study with 4‐year follow‐up. Issue 11 (27th May 2020) - Moh, A.; Seah, N.; Low, S.; Ang, K.; Sum, C. F.; Subramaniam, T.; Kwan, P. Y.; Lee, S.; Tang, W. E.; Lim, S. C.
Abstract: Aim: To investigate the association between baseline plasma zinc‐α2‐glycoprotein and non‐albuminuric chronic kidney disease progression in type 2 diabetes. Methods: Adults with normoalbuminuria at entry ( n =341; age 57±10 years, 52% men) were analysed. Chronic kidney disease progression was defined as a decrease in chronic kidney disease stage and a decline of ≥25% in estimated GFR from baseline. Baseline plasma zinc‐α2‐glycoprotein levels were quantified by immunoassay, and analysed either as a continuous variable or by tertiles in Cox proportional hazards models. Model discrimination was assessed using Harrell's C‐index. A sensitivity analysis was performed on a subset of individuals who maintained normoalbuminuria during follow‐up. Results: Chronic kidney disease progression occurred in 54 participants (16%). Zinc‐α2‐glycoprotein levels were elevated in chronic kidney disease progressors ( P = 0.011), and more progressors were assigned to the higher zinc‐α2‐glycoprotein tertile than non‐progressors. In the unadjusted Cox model, zinc‐α2‐glycoprotein, both as a continuous variable (hazard ratio 1.72, 95% CI 1.08–2.75) and tertile 3 (vs tertile 1; hazard ratio 2.14, 95% CI 1.10–4.17), predicted chronic kidney disease progression. The association persisted after multivariable adjustment. The C‐index of the Cox model increased significantly after incorporation of zinc‐α2‐glycoprotein into a base model comprising renin‐angiotensin system antagonist usage. Sensitivity analysis showed that zinc‐α2‐glycoprotein independently predicted chronic kidney disease progression among individuals who maintained normoalbuminuria during follow‐up. Conclusions: Plasma zinc‐α2‐glycoprotein is associated with chronic kidney disease progression, and may serve as a useful early biomarker for predicting non‐albuminuric chronic kidney disease progression in type 2 diabetes. What's new?: A substantial proportion of individuals with type 2 diabetes experience a decline in GFR without significant albuminuria, which is termed non‐albuminuric chronic kidney disease (CKD). Early biomarkers predictive of non‐albuminuric CKD progression are needed but are currently lacking. Previous limited cross‐sectional studies have presented an association between zinc‐α2‐glycoprotein (ZAG) and non‐albuminuric CKD in type 2 diabetes. Our findings showed that baseline plasma ZAG independently predicted non‐albuminuric CKD progression in adults with type 2 diabetes over 4 years. ZAG may serve as a useful early biomarker for predicting CKD progression in this distinct subgroup of individuals with normoalbuminuria.